2002
DOI: 10.1124/mol.61.5.1017
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Treatments Induce the Expression of Basic Fibroblast Growth Factor in Cortical and Hippocampal Neurons

Abstract: New experimental evidence suggests that the mechanism of action of antidepressants includes the induction of neurotrophic factor synthesis in selected brain areas. The present study is aimed at establishing whether prolonged antidepressant treatments increase the expression of basic fibroblast growth factor (FGF2), a polypeptide growth factor that has a broad neurotrophic activity in the adult central nervous system. Rats received a single dose or long-term (3 weeks) administration of desipramine (DMI), fluoxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 38 publications
4
87
1
Order By: Relevance
“…Yet, a number of medications and drugs have been shown to increase the expression of multiple growth factors. Antidepressants for example, have been shown to increase the expression of IGF-1, BDNF, and FGF-2 (Duman et al, 1997;Mallei et al, 2002;Khawaja et. al., 2004;Maragoli et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, a number of medications and drugs have been shown to increase the expression of multiple growth factors. Antidepressants for example, have been shown to increase the expression of IGF-1, BDNF, and FGF-2 (Duman et al, 1997;Mallei et al, 2002;Khawaja et. al., 2004;Maragoli et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, BDNF has been shown to inhibit, apoptosis in hippocampal neurons Johnson-Farley et al, 2006). Expression of FGF-2, a less well characterized growth factor, has also been reported to be increased by antidepressants in cortex and hippocampus (Mallei et al, 2002;Maragnolli et al, 2004). The peptide has been demonstrated to have a role in stimulating hippocampal neurogenesis (Palmer et al, 1999) and, and in some model systems, has been reported to have neurotrophic actions.…”
Section: Introductionmentioning
confidence: 98%
“…Antidepressants increase the expression of these neurotrophic/growth factors [15,16,17,18,19] and BDNF and VEGF mediate the action of antidepressants on neurogenesis in the adult DG in vivo [19,20]. However, it remains unclear whether FGF2, GDNF and IGF mediate the effect of antidepressants on neurogenesis on the adult DG.…”
Section: Introductionmentioning
confidence: 99%
“…Antidepressant drugs and chronic electroconvulsive shock treatment may increase the expression of fibroblast growth factor-2 (FGF-2) in frontal cortices and hippocampus (Mallei et al, 2002;Maragnoli et al, 2004), suggesting that potentially also the FGF-2 expression could mediate the antidepressant effects, in line with these results chronic antidepressant treatment increases neurogenesis in adult rat hippocampus (Duman et al, 2001) and recently evidence has been provided that increased neurogenesis might play a role in the mechanism of antidepressant drug action (Santarelli et al, 2003). Depression is associated with reduced cortical thickness and neuronal size (Rajkowska et al, 1999) and may even be caused by cortical neuronal atrophy with the accompanying loss of neuronal communication in prefrontal cortex.…”
Section: Neurotrophic Factorsmentioning
confidence: 99%